Konsep Pendidikan Jasmani, Akal dan Hati dalam Perspektif HAMKA - Rochim, Rochim (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2017)
In the fast globalization era, Islamic education donâ€™t has standard concept in itâ€™s application. It is proven by the existence of Islamic education quality that lower than other education. Thus, it is needed a comprehensive educational concept in developing all the potential that exists in humans i.e. heart, mind, and physic. The results of this study suggest that (1) According to HAMKA, Islamic education should develop an innate human potential itself, which includes the heart, mind and physical. Heart needed to keep human understand the good and avoid the bad deeds, mind needed to get the knowledge so that they can understang the good and bad things, heart and mind can be perfect when supported by a healthy physical. (2) The potential synergies of heart, mind and physical is a tool that support the function of human life as the Caliph fi-al-ard. (3) The implications of synergy between the heart, mind, and physical will make human have noble, intelligent, and capable to change the world order with their skill.